Heat-acclimatised strains of Rhodopseudomonas palustris reveal higher temperature optima with concomitantly enhanced biohydrogen production rates. (23rd March 2021) - du Toit, Jan-Pierre; Pott, Robert W.M.
Abstract: Temperature is a critical parameter for bioprocess performance, requiring careful optimisation for peak efficiency. Green biohydrogen production via photofermentation by purple nonsulfur bacteria including Rhodopseudomonas palustris has been extensively researched, yet realisation is limited by comparatively low productivity. We thus assessed the growth and hydrogen productivity of two closely-related strains of R. palustris acclimated to higher temperatures, revealing markedly increased strain-dependent optima than the 30 °C previously accepted. Strain CGA009 grew 53% faster at 35 °C, with 2.4-fold higher hydrogen production rate, while at 40 °C strain ATH 2.1.37 displayed 86% faster growth and 4-fold higher production rate, along with improved specific production and substrate conversion efficiency. These results reaffirm the necessity of pre-acclimation when verifying temperature optima and expand the feasible temperature range for advancement of high-rate biohydrogen production. Further, the superior heat resistance and production capability of strain ATH 2.1.37 raises the potential for further efficiency gains from thermotolerant environmental isolates. Highlights: Temperature significantly influences growth and hydrogen production rate. Heat-acclimated Rhodopseudomonas palustris strains showed higher temperature optima. At 40 °C strain ATH2.1.37 showed up to 4-fold higher hydrogen production versus 30 °C. Despite 99.9% similarity, strain ATH2.1.37 had 5 °C higher optimum than CGA009. Prior 30 °C peak likely an artefact of mild long-term laboratory growth conditions.